An activatable NIR‐II fluorescent probe for tracking heavy‐metal ion and high‐level salt‐induced oxidative stress in plant sprouts. Issue 2 (27th October 2022) - Long, Yi; Chen, Junjie; Zeng, Fang; Wu, Shuizhu
Abstract: Humans and plants have become enfolded and inseparable. Abiotic stresses in particular oxidative stress caused by heavy‐metal ions or high‐level salt contamination deleteriously impact plants' growth process and have become a major threat to sustaining food security. Sprouting is the first step in plants' growth process. When plant sprouts endure oxidative stress induced by toxic heavy‐metal ions or high‐level salt, accelerated generation of reactive oxygen species (e.g., H2 O2 ) occurs inside plant sprouts; hence in‐situ H2 O2 in plant sprouts could serve as the in‐vivo biomarker for tracking the oxidative stress in plant sprouts. Herein, we design an activatable probe CT‐XA‐H2 O2 to track the oxidative stress in plant sprouts via in vivo NIR‐II fluorescent imaging. In CT‐XA‐H2 O2, cyano‐thiazole acts as the electron‐accepting moiety and xanthane‐aminodiphenyl as the electron‐donating moiety, and dioxaborolane as the biomarker‐responsive unit and fluorescence quencher. The probe CT‐XA‐H2 O2 shows weak fluorescent emission. When H2 O2 is present, the dioxaborolane in the probe is cleaved, consequently, the dye CT‐XA‐OH is generated and brings about significant fluorescent signals for detecting and imaging the in‐situ biomarker. Moreover, the aminodiphenyl group endues the chromophore (the activated probe) with aggregation‐induced emission characteristics, which ensures stronger fluorescence in the aggregated state in the aqueous milieu. The probe CT‐XA‐H2 O2 has been employed in the Cd 2+ ‐ion or high‐level salt (NaCl) induced oxidative stress models of soybean sprouts and peanut sprouts, and the experimental results evidently reveal the probe's ability for in‐situ biomarker‐activatable in‐vivo detection and imaging in the plants' sprouts. Abstract : The biomarker‐activatable probe (CT‐XA‐H2 O2 ) has been designed for tracking the Cd 2+ ‐ion or NaCl‐induced oxidative stresses in soybean/peanut sprouts by responding to in‐situ biomarker H2 O2 via NIR‐II fluorescent imaging. The aggregation‐induced emission feature of the activated probe (CT‐XA‐OH) ensures stronger fluorescence in the aggregated state in the aqueous milieu. The results could provide warning/monitoring for the Cd 2+ ‐ion or NaCl‐induced oxidative stress.